2007
DOI: 10.1002/mrd.20785
|View full text |Cite
|
Sign up to set email alerts
|

Osmolarity at early culture stage affects development and expression of apoptosis related genes (bax‐α and bcl‐xl) in pre‐implantation porcine NT embryos

Abstract: This study examined whether high osmolarity of culture medium at the early culture stage affects development and expression of apoptosis related genes (Bax-alpha and Bcl-xl) of porcine nuclear transfer (NT) and in vitro fertilization (IVF) embryos. NT and IVF embryos were divided into three groups and the basic medium was PZM-3 (260-270 mOsmol, control group). The control group of embryos was cultured in PZM-3 for whole culture period. Other two groups of embryos were cultured in a modified PZM-3 with 0.05 M s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…The evaporation increased osmolality and salt concentration, which is harmful to oocyte and embryo viability. Regardless of the evidence that high osmolality during early embryonic stages decreases the number of apoptotic cells and improves blastocyst formation, the increase in osmolality is highly detrimental for later stages of embryo development (Nguyen et al, 2003;Hwang et al, 2008). Bovine embryos require a low constant osmolality, near 270 mOsm kg -1 (reviewed by Wright and Bondioli, 1981).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The evaporation increased osmolality and salt concentration, which is harmful to oocyte and embryo viability. Regardless of the evidence that high osmolality during early embryonic stages decreases the number of apoptotic cells and improves blastocyst formation, the increase in osmolality is highly detrimental for later stages of embryo development (Nguyen et al, 2003;Hwang et al, 2008). Bovine embryos require a low constant osmolality, near 270 mOsm kg -1 (reviewed by Wright and Bondioli, 1981).…”
Section: Resultsmentioning
confidence: 98%
“…There is some evidence that osmolality of culture medium must remain stable during all the IVP process (Kruger et al, 1985). However, recent data indicates that increased osmolality in the first two days of culture improved in vitro development and reduced apoptosis through regulation of Bax-alpha/Bclxl gene expression in porcine embryos (Hwang et al, 2008). Osmotic stresses can also damage DNA, affect DNA replication, DNA transcription and mRNA translation, leading to cellular damage (Burg et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…These results demonstrate that the optimal osmolarities required before and after early cleavage for the parthenogenetic development of pig oocytes are different. Recent reports have indicated that there is a preference for physiological osmolarities during the first 2 to 3 days of culturing pig in vitro -fertilized embryos [13], activated oocytes [20,21,22] and SCNT embryos [14, 21, 22], although the oocytes/embryos have to be transferred into hypotonic media subsequently in order to maintain in vitro development. The results of the present study are consistent with these reports.…”
Section: Discussionmentioning
confidence: 99%
“…When cultured in isotonic media during the first 2 days, the development of pig electrically activated oocytes and SCNT embryos improved because of the reduction in their fragmentation rates [21]. The same culture conditions also reduced apoptosis in pig SCNT embryos, resulting in improved development [14]. These results suggest that culture in hypotonic media induces excessive apoptosis and fragmentation in pig oocytes and embryos compared with isotonic media because of unphysiological conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation